Long-term antidepressant treatment for negative symptoms in schizophrenia: the actions study - Barnes, T; Leeson, V; Paton, C; Osborn, D; Killaspy, H; Craig, T; Lewis, S; Keown, P; Ismail, S; Crawford, M; Baldwin, D; Lewis, G; et al. (Oxford University Press, 2017)
The negative symptoms of schizophrenia represent deficiencies in emotional responsiveness, motivation and socialization that tend to be persistent despite standard antipsychotic treatment. Two sub-domains of expressive deficits (affective flattening and poverty of speech) and avolition-amotivation for daily-life and social activities (apathy, amotivation and asociality) are recognized. Reviews of randomized controlled trials of adjunctive antidepressant treatment have concluded that the combination of antipsychotics and antidepressants may be effective in treating the negative symptoms of schizophrenia, but the amount and quality of the evidence available do not allow for any robust conclusion about the potential risks and benefits of such a strategy.